Public service broadcasting the challenges of the twenty-first century - Atkinson, Dave (No. III)
This is a study of public service broadcasting which explores how it can maintain and strengthen its legitimacy against the dictates of a market driven logic, and contribute to social and cultural development. It features case studies from 16 countries, both industrial and developing.